Development and Implementation of a COVID-19 Disease Response Protocol at a Large Academic Medical Center. (22nd December 2020) - Maxam, Meshell; DeRonde, Kailynn J.; Vega, Ana D.; Skiada, Dimitra; Vu, Christine A.; Salazar, Veronica; Boatwright, Renata; Cano-Casillas, Ennie; Goodnow, Venessa; Sposato, Kathleen A.; Paige, Peter G.; Zambrana, David; et al.
ABSTRACT: In response to the rapid spread of novel coronavirus disease 2019 (COVID-19), health-care systems should establish procedures for early recognition and management of suspected or confirmed cases. We describe the various steps taken for the development, implementation, and dissemination of the interdisciplinary COVID-19 protocol at Jackson Health System (JHS), a complex tertiary academic health system in Miami, Florida. Recognizing the dynamic nature of COVID-19, the protocol addresses the potential investigational treatment options and considerations for special populations. The protocol also includes infection prevention and control measures and routine care for suspected or proven COVID-19 patients.